2021
DOI: 10.1007/s00281-021-00875-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of cell death in parasitic infections

Abstract: For a long time, host cell death during parasitic infection has been considered a reflection of tissue damage, and often associated with disease pathogenesis. However, during their evolution, protozoan and helminth parasites have developed strategies to interfere with cell death so as to spread and survive in the infected host, thereby ascribing a more intriguing role to infection-associated cell death. In this review, we examine the mechanisms used by intracellular and extracellular parasites to respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 102 publications
0
6
0
4
Order By: Relevance
“…Multiple pairs of 'eat me' signals and receptors might be involved in macrophage-mediated efferocytosis in infectious diseases 30 . We previously investigated the role of the αvβ3 integrin in vitro and found that: i) peritoneal macrophages from T. cruzi-infected mice phagocytosed apoptotic naïve T cells in an integrin-dependent fashion, and ii) αvβ3-mediated efferocytosis exacerbated T. cruzi infection by inducing PGE-2, TGF-β, ornithine decarboxylase activity and polyamine production 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple pairs of 'eat me' signals and receptors might be involved in macrophage-mediated efferocytosis in infectious diseases 30 . We previously investigated the role of the αvβ3 integrin in vitro and found that: i) peritoneal macrophages from T. cruzi-infected mice phagocytosed apoptotic naïve T cells in an integrin-dependent fashion, and ii) αvβ3-mediated efferocytosis exacerbated T. cruzi infection by inducing PGE-2, TGF-β, ornithine decarboxylase activity and polyamine production 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the phagocytosis of apoptotic cells (efferocytosis) by infected macrophages exacerbated T. cruzi infection in a TGF-βand polyamine-dependent manner 13 . Therefore, inhibitors of apoptosis and efferocytosis are potential therapeutic tools to potentiate immune responses to some parasite infections 21,[28][29][30] . Among the receptors involved in efferocytosis, TAM (Tyro3, Axl, and Mer) tyrosine kinase (TK) receptors 31,32 are especially promising as molecular targets because new selective inhibitors for Axl or Mer signalling have been used in clinical trials to treat cancer 33 .…”
mentioning
confidence: 99%
“…The review by Bosurgi and Rothlin in this issue addresses the management of cell death in the context of parasitic infections [4]. The authors show that the recognition and phagocytosis of dead cells are of a major relevance for shaping the immune response.…”
Section: Homoeostatic Inflammation Vs Pathogenic Tissue Remodellingmentioning
confidence: 99%
“…Parasites, including protozoans and helminthes, have developed evolutionary strategies that can interfere with cell death to survive and multiply inside the host tissues [ 23 ]. Many studies suggested that C. parvum has multiple strategies to control apoptosis to facilitate its growth and life cycle completion.…”
Section: Introductionmentioning
confidence: 99%